KUALITAS E-LKPD BERBASIS ANDROID DALAM MENULIS TEKS CERPEN BAGI SISWA KELAS XI SMA - Chintya Gusti Yulanda; Mangatur Sinaga; Silvia Pertamasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Research on the Quality of Electronic - Student Worksheets (E-LKPD) based on android aims to determine the quality of products in the form of Electronic - Student Worksheets which are used as media for teaching materials that can assist students in developing short stories texts. That way, students tend to have no difficulty in the learning process of short story writing skills. This android-based E-LKPD can also help teachers to measure the ability of students in writing short stories with interesting and latest learning media. This research is research and development (R&D). The data analysis technique used is quantitative description. The results showed that the Electronic-Student Worksheet writing android-based short stories was appropriate to be used as a companion to teaching materials. The validation results from media experts stated that E-LKPD writing short stories based on android was feasible to use with a percentage of 88.3%, while from linguists it reached a feasibility with a percentage of 88.6%. The feasibility test of field experts got a percentage of 93.3% and the trial on class XI students of SMAN 1 Bangkinang was obtained with a percentage of 88.5%.Key Word: Quality,E-LKPD,Writing Short Stories